The Fabrication of Automobile Components by Applying Electromagnetic Stirring in Semisolid Process - H. H. Kim; C. G. Kang (Advances in Materials Science and Engineering, 2011)
This paper describes a rheo-forming process for the development of automobile components, such as knuckle, by using rheology material with electromagnetic stirring (EMS) system equipment. The effects of several process and metallurgy parameters such as stirring current, stirring time, pouring temperature, forming pressure, tip velocity, fraction of primary phase, and its morphology and distribution, on the final products are reviewed and discussed. A variety of simulation studies are conducted. In addition, the effect of the vacuum-assisted method on the performance of rheo-forged products is introduced. The EMS is an effective process to improve a feed stock in the rheo-forming process with improved mechanical properties.